2013
DOI: 10.1002/jemt.22270
|View full text |Cite
|
Sign up to set email alerts
|

Tridimensional quantitative porosity characterization of three set calcium silicate‐based repair cements for endodontic use

Abstract: The aim of the this study was to quantitatively evaluate in three-dimensional (3D), the porosity degree of three improved silicate-based endodontic repair cements (iRoot BP Plus®, Biodentine®, and Ceramicrete) compared to a gold-standard calcium silicate bioactive cement (Pro Root® MTA). From each tested cement, four samples were prepared by a single operator following the manufacturer's instructions in terms of proportion, time, and mixing method, using cylindrical plastic split-ring moulds. The moulds were l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 14 publications
2
35
1
3
Order By: Relevance
“…Another study on porosity was one by De Souza et al [21] where Biodentine was compared to other silicate based cements, IRoot BP Plus, Ceramicrete, and ProRoot MTA using micro—CT characterization. The authors indicated that no significant difference in porosity between IRoot BP PlusVR, BiodentineVR, and Ceramicrete were observed.…”
Section: Physical Properties Of Biodentinementioning
confidence: 99%
“…Another study on porosity was one by De Souza et al [21] where Biodentine was compared to other silicate based cements, IRoot BP Plus, Ceramicrete, and ProRoot MTA using micro—CT characterization. The authors indicated that no significant difference in porosity between IRoot BP PlusVR, BiodentineVR, and Ceramicrete were observed.…”
Section: Physical Properties Of Biodentinementioning
confidence: 99%
“…In order to minimize these errors, all reconstructions were performed using the artifact reduction tools. De Souza et al 10 proposed a standard to obtain the threshold, using known values for the porosity of each material. Therefore, the use of microcomputed tomography for porosity analysis also presents variations that must suggest patterns based on the experiment performed and type of sample.…”
Section: Discussionmentioning
confidence: 99%
“…2017 Nov-Dec; 46(6): 362-367 366 evaluation of these faults 10 . Microtomography has been used to evaluate the porosity of different materials 8,9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this distinction is not always clear in the literature. Calcium silicate was used in another experimental magnesium phosphate dental product [32,79,93]. The calcium silicate was not a hydraulic phase but a phase that reacted in situ contributing to bioactivity.…”
mentioning
confidence: 99%